2006
DOI: 10.1007/s00778-005-0169-1
|View full text |Cite
|
Sign up to set email alerts
|

Attribute grammars for scalable query processing on XML streams

Abstract: We introduce the notion of XML Stream Attribute Grammars (XSAGs). XSAGs are the first scalable query language for XML streams (running strictly in linear time with bounded memory consumption independent of the size of the stream) that allows for actual data transformations rather than just document filtering. XSAGs are also relatively easy to use for humans. Moreover, the XSAG formalism provides a strong intuition for which queries can or cannot be processed scalably on streams. We introduce XSAGs together wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Streamed evaluation means here that only one pass over the XML stream is used, and progressive evaluation means that the answers are output as soon as possible. Current streamed query processors, e.g., [8]- [14], are not designed to accomplish all these desiderata, their focus being in most cases a subset of them, possibly with additional desiderata, e.g., support for indexing and evaluating large sets of simple queries. We survey these processors in Section IX.…”
mentioning
confidence: 99%
“…Streamed evaluation means here that only one pass over the XML stream is used, and progressive evaluation means that the answers are output as soon as possible. Current streamed query processors, e.g., [8]- [14], are not designed to accomplish all these desiderata, their focus being in most cases a subset of them, possibly with additional desiderata, e.g., support for indexing and evaluating large sets of simple queries. We survey these processors in Section IX.…”
mentioning
confidence: 99%
“…More recently, it has been shown they are useful also for XML, and in particular for query languages and query processing (see, for instance, [39,41,40,29]). Extensive reviews of attribute grammar theory, implementation, systems, and applications are given in, e.g., [9,8,28,1,43].…”
Section: Related Workmentioning
confidence: 99%
“…LR-AGs have been used in the context of XML streaming [13] and already Bochman [26] showed that all attribute values of an LR-AG can be computed in one left-to-right pass through the input tree. Accordingly, LR-AGs seem a natural candidate in our context.…”
Section: Factmentioning
confidence: 99%